Theoretical models to guide undergraduate medical curriculum development: an integrative review - Xin Yin; Luo Wang; Qiu Li; Jiachen Han; Fang Zhou; Shuo Wang (BMC Medical Education)
Abstract Background Higher medical education has experienced significant growth in recent years. Curriculum development has consistently been the focus of educators’ investigation, as it is one of the most critical components of educational reform. High-quality curriculum development must be founded on educators’ knowledge and experience and supported by scientific and standardized theoretical models. Objective To integrate a comprehensive development framework based on the key steps and components of theoretical models that guide undergraduate medical curriculum development, and to summarize the issues that need attention in curriculum development. Methods Adheres to the WHITTEMORE and KNAFL frameworks. Eight databases were queried: PubMed, Embase, The Cochrane Library, Web of Science, CINAHL, CNKI, Wanfang, and VIP. The inclusion criteria encompassed research that employed a theoretical model to inform the development of an undergraduate medical curriculum, detailed the development process, and was published in English or Chinese. Two researchers independently screened the titles, abstracts, and entire texts. The methodological quality of empirical studies was evaluated using the Mixed Methods Assessment Tool (MMAT). Results This review encompassed 18 articles, comprising three qualitative studies, six quantitative studies, and nine mixed-methods studies. Ten theoretical models that may guide curriculum development are mentioned in the 18 articles. We have integrated them into a comprehensive theoretical framework comprising four essential steps: situational analysis of curriculum development, delineation of curriculum objectives, design of curriculum material, and implementation and assessment of the curriculum. Of the 13 studies examining course delivery effectiveness, prevalent evaluation methods comprised quantitative assessments and qualitative feedback. The qualitative feedback revealed that inadequate course planning, a scarcity of offline practical activities, and unsuitable teaching material selection were the primary factors influencing course satisfaction. Conclusion This review provides an overview of the theoretical models that guide medical curriculum development and their essential components, thereby establishing a comprehensive curriculum development framework and summarizing issues that require attention during curriculum development. The findings provide evidence-based guidance for model selection, methodological evaluation, and curriculum improvement.